Robinson Crusoe - Defoe, Daniel (Penguin readers, 2008)
The book tells the story of Robinson Crusoe who is at sea when there is a big storm. His ship goes down, and his friends die. The sea throws Crusoe onto a beach. He is on an island. But which island? Are there other people on it? And are they friendly? What will Crusoe do now?